Digital Islamic Financial Literacy: Edukasi Keuangan Syariah Guna Menyikapi Maraknya Pinjaman Online pada SMK Muhammadiyah Jember - Ari Sita Nastiti; Lutfi Ali Muharom; Moh. Halim (Universitas Muhammadiyah Jember, 2026)
The rapid development of digital financial services has expanded access to financial transactions for various groups, including secondary school students. Alongside these benefits, emerging challenges include limited understanding of digital financial mechanisms, risks related to personal data security, and increased exposure to online lending services. In Islamic-based educational environments, strengthening financial literacy aligned with sharia principles is essential to provide students with value-based guidance in financial decision-making.This community service program aimed to enhance students’ and teachers’ understanding of digital financial literacy, fundamental principles of Islamic finance, and the risks associated with online lending. The program was implemented at SMK Muhammadiyah Jember, involving approximately 60 participants consisting of students and teachers. The activities were conducted through interactive lectures, group discussions, simple case simulations, and evaluation using pre-test and post-test instruments. The results indicate an improvement in participants’ understanding of digital financial concepts, Islamic financial principles, and awareness of online lending risks. Participants demonstrated better ability to distinguish needs from wants, apply sharia principles in financial decision-making, and identify characteristics of safe digital financial services. This program contributes to strengthening sharia-based financial literacy in the school environment and highlights the importance of collaboration between higher education institutions and schools in fostering responsible financial behavior in the digital era